COMPARATIVE ANALYSIS OF PIPELINE ACCIDENTS ACROSS RUSSIA AND THE USA - A P Oleinik (RUDN Journal of Ecology and Life Safety, 2015)
Analysis of contemporary accident rates on pipeline transport facilities is one of the major decision- making procedures for protection, including the quantitative assessment of risk, modelling of hazardous substances emissions and safety criteria justification. The information provided in the state authorities reports across Russia and the US have been analysed to identify overall trends in accident rates, including the influence of the modern safety provisions.